Pengaruh Konten Instagram Yonex terhadap Minat Beli Konsumen - Rifqi Widyan Farhan; Oktaviana Purnamasari (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
In the highly competitive sports equipment market, particularly for badminton items, businesses must rely not only on high-quality products but also on efficient digital media marketing techniques. Brands frequently utilize Instagram, a visual social media site, to enlighten consumers about their products and pique their interest. Yonex uses Instagram with the account @yonex_badminton. Nevertheless, a large following and frequent posting may not always indicate how well a piece of content stimulates customer interest in making a purchase. The purpose of this study is to examine how @yonex_badminton Instagram content affects consumer interest in making purchases. With the use of statistical software, this study employs a quantitative methodology that includes survey procedures and data analysis utilizing basic linear regression. 84 responders who followed the @yonex_badminton Instagram account made up the research sample. With a t-value of 13.387 and a significance value of 0.000, the results demonstrated that Instagram content had a favorable and substantial impact on customer purchase interest. Instagram content may account for 68.6% of the variance in customer purchase interest, according to the coefficient of determination (R2) value of 0.686. Other factors that are not within the purview of this study account for the remaining 31.4%. This research gives a broad overview of how managing regular, engaging, and educational Instagram content may be a useful digital marketing tactic and boost customer interest in making a purchase.